1982
DOI: 10.1016/s0021-9673(00)84852-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between liquid chromatographic capacity ratio data on lichrosorb RP-18 and partition coefficients in the octanol—water system

Abstract: SUMMARYRetention data of methylbenzenes, n-alkylbenzenes, fused arenes, polyphenyls, chlorobenzenes, -anilines and -phenols and some polar monosubstituted benzenes have been measured on LiChrosorb RP-18, using methanol-water mixtures as eluents at 25'C.The important effect of solute activity coefficients in water on capacity ratio (k) data, holding for water as eluent, and on partition coefficients in the octanol-water system (PO,,_) is shown. The log k-log I',,,,_ correlation is improved by using (1inearIy ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…The acidity of PFASs enables electronic and hydrogen bond interactions with the silanol groups in the stationary phase to occur [11,17,19,21] (instead of, or complementary to, van der Waals interactions). This non-linear behaviour may be enhanced at high methanol fractions in the mobile phase.…”
Section: Elution Behaviour At High Methanol Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidity of PFASs enables electronic and hydrogen bond interactions with the silanol groups in the stationary phase to occur [11,17,19,21] (instead of, or complementary to, van der Waals interactions). This non-linear behaviour may be enhanced at high methanol fractions in the mobile phase.…”
Section: Elution Behaviour At High Methanol Fractionsmentioning
confidence: 99%
“…Several authors have demonstrated [19][20][21] that for neutral compounds the quadratic term can be neglected if methanol is used as the organic modifier. Hence, the following equation results:…”
Section: Introductionmentioning
confidence: 99%
“…A basic re-quirement is a theoretical model connecting the chromatographic retention parameter to the partition constant. In its most simple form this model may be a monolinear Collander-type regression relationship as used for the determination of the partition coefficient between noctanol and water (Kow) and the HPLC reversed-phase capacity factor (k') for series of compounds [1].…”
Section: Introductionmentioning
confidence: 99%
“…All capacity factors were determined at four compositions of the mobile phase and extrapolated to 100°70 water, yielding k0, following the recommendations by Hammers et al (1982). The HPLC-apparatus used consisted of a Pye Unicam 4010 double piston pump operated at 1 ml/min flow and a Pye Unicam 4020 UVdetector, operated at 254 nm.…”
Section: Determination Of Hplc Capacity Factorsmentioning
confidence: 99%